Serologic and Molecular Diagnosis of Human Parvovirus B19 in Rheumatoid Arthritis Patients - Özlem Solak; Mustafa Altındiş; Hasan Toktaş; Ümit Dündar; Reşit Köken; Aycan Türel; Nedim Tunç; Vural Kavuncu (Archives of Rheumatology, 2009)
Objective: To investigate Human Parvovirus (HPV) B19 IgG and IgM antibody levels and B19 viral DNA using PCR method in the serum of Rheumatoid arthritis (RA) patients to determine the role of B19 in the ethiopathogenesis of RA. Material and Methods: Sixty patients who met the criteria of American Rheumatism Association for RA and who were followed in our outpatient clinic, 2 patients with a diagnosis of Juvenile RA and 29 patients with a diagnosis of osteoarthritis (OA) as control group were included in the study. Peripheral venous blood sample was obtained from the patients to investigate IgG and IgM against HPV B19. HPV B19 IgM and IgG were investigated using micro Enzyme Linked Immunosorbent Assay method. B19 viral DNA isolation was performed using Real Time PCR. Results: Ages and sex were not different between groups (p>0.05). HPV B19 IgM positivity was determined in 7 (%11.3) in RA and in 4 (%13.8) patients in OA group (p>0.05). B19 IgG positivity was determined in 29 (%46.8) in RA and in 17 (%58.6) patients in OA group (p>0.05). B19 DNA was investigated using PCR in 10 patients among 11 patients who had B19 IgM positivity. B19 DNA was isolated in 5 of 7 (%71.4) RA patients who were positive for B19 IgM. But no B19 DNA could be isolated in 3 osteoarthritis patients. Although B19 DNA was isolated markedly higher in RA group, the difference was not significant between groups because B19 IgM was positive in a small number of patients (p>0.05). Conclusion: We found the incidence of HPV B19 IgM and IgG in the serum of RA patients not different from OA patients. We assessed viral DNA positivity by PCR as reinfection in former cases. We believe that we will get clear evidence about the role of B19 in RA by gathering the results of different studies. (Turk J Rheumatol 2009; 24: 17-20)